2019
DOI: 10.1038/s41416-019-0566-7
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-222 reprogrammed cancer-associated fibroblasts enhance growth and metastasis of breast cancer

Abstract: Background Cancer-associated Þbroblasts (CAFs) are known to impact on tumour behaviour but mechanisms controlling this are poorly understood. Methods Breast normal fibroblasts (NFs) or CAFs were isolated from cancers by laser-microdissection or were cultured. Fibroblasts were transfected to manipulate miR-222 or Lamin B Receptor (LBR). Fibroblast conditioned medium was collected and used to treat epithelial BC lines MDA-MB-231 and MDA-MB-157. Migration, invasion, proliferation, or senescence was assessed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 48 publications
1
29
0
Order By: Relevance
“…On the other hand, Zhang Y. et al focused on the downregulation of miR-101 in CAFs with consequent upregulation of CXCL12, enabling lung cancer cells to proliferate, migrate, and invade [ 64 ]. Chatterjee A. and collaborators identified the upregulation of miR-222 in CAFs with respect to normal fibroblasts (NFs) and observed that the inhibition of miR-222 could impair the CAF-dependent progression of breast cancer cells [ 65 ]. Santolla M.F.…”
Section: Ncrna In Immune Escapementioning
confidence: 99%
“…On the other hand, Zhang Y. et al focused on the downregulation of miR-101 in CAFs with consequent upregulation of CXCL12, enabling lung cancer cells to proliferate, migrate, and invade [ 64 ]. Chatterjee A. and collaborators identified the upregulation of miR-222 in CAFs with respect to normal fibroblasts (NFs) and observed that the inhibition of miR-222 could impair the CAF-dependent progression of breast cancer cells [ 65 ]. Santolla M.F.…”
Section: Ncrna In Immune Escapementioning
confidence: 99%
“…MiR-200s regulate collagen contraction by CAFs as well as trigger ECM remodeling, invasion, and tumor metastasis [ 517 ]. Similarly, miR-222 regulates CAFs’ reprogramming and its overexpression promotes fibroblast-induced cancer cell migration and invasiveness [ 518 ].…”
Section: Tumor–stroma Interactionsmentioning
confidence: 99%
“…This was also found to promote angiogenesis through a VEGF-independent pathway. CAFs demonstrate increased miR-222 expression relative to normal fibroblasts, which was found to increase migration, invasion and senescence and lead to CAF activation through its depletion of lamin B receptor (LBR) [ 115 ]. Regulation of LBR-induced senescence and induction of EMT were mechanisms that were associated with the miR-222–LBR axis.…”
Section: Mirnas In Triple-negative Breast Cancermentioning
confidence: 99%